Ruling on breastfeeding in Islamic jurisprudence - األستاذ المساعد الدكتور هاشم محمدامين سليمان (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
“The Islamic ruling of the stallion feeding in Islamic juris prudence” the research studies the indirect feeding of a bady by aman with the help of his wife. The wife directly feeds the body. And thus the body is forbidden to the woman and her children (i.e). they cannot marry his/her. Also, the husband is for bidden to the body. Because with out her husband. The woman do not have the milk and cannot feed. Islamic scientists have different view points concerning this issue. Some of them believe that the breast feeding is not related to the husband, and thus, the body is not forbidden to the man, and others who feeds him/her, as well as to her husband and children.